2013
DOI: 10.1902/jop.2012.110467
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory and Anti‐Inflammatory Cytokines in Gingival Crevicular Fluid and Serum of Patients With Rheumatoid Arthritis and Patients With Chronic Periodontitis

Abstract: Although clinical periodontal disease parameters indicated more severe periodontal disease in CP compared to RA patients, immunologic evaluation did not reveal consistent results regarding proinflammatory and anti-inflammatory cytokine levels. This might be a result of the use of non-steroidal anti-inflammatory drugs and rheumatoid agents by patients with RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
76
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 53 publications
(101 reference statements)
10
76
1
3
Order By: Relevance
“…However, the prevalence of moderate to severe periodontitis in controls was also high (69%) and not significantly different. Likewise, some other studies reported no significant differences in periodontitis prevalence between RA patients and controls [10][11][12][13][14] , which also might be (partly) due to the potent anti-inflammatory medications used by the RA patients 15,16 . The vast majority of studies did find a higher prevalence of periodontitis in RA patients as compared to controls 2,[6][7][8] , It has to be noted that the patients in these studies, like in our study, were taking antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, the prevalence of moderate to severe periodontitis in controls was also high (69%) and not significantly different. Likewise, some other studies reported no significant differences in periodontitis prevalence between RA patients and controls [10][11][12][13][14] , which also might be (partly) due to the potent anti-inflammatory medications used by the RA patients 15,16 . The vast majority of studies did find a higher prevalence of periodontitis in RA patients as compared to controls 2,[6][7][8] , It has to be noted that the patients in these studies, like in our study, were taking antiinflammatory drugs.…”
Section: Discussionmentioning
confidence: 91%
“…Both diseases share risk factors and have pathological pathways in common, resulting in loss of function and disability as a final clinical outcome 35 . As such, drugs used for RA have also been reported to reduce periodontitis severity 11,15,16 . About eighty percent of the RA patients in our study were on corticosteroids (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations